The correlation between interleukin-1β levels and aggressive periodontitis: A scoping review - Agus Susanto; Yanti Rusyanti; Nu’ty Hasya Chinta Andari Effendi (Scientific Dental Journal, 2023)
Aggressive periodontitis is a multifactorial disease; the body’s immune response is one of the factors that contributed to the disease development. One of the responses is in the form of the secretion of cytokines—that is, interleukin1β (IL-1β). The secretion of the said cytokine influences the development of periodontitis,particularly the occurrence of rapid bone loss. This study aimed to confirm whether there is a correlation between the levels of IL-1β and the severity of aggressive periodontitis from collected sources. The research performed is a type of literature review that employs the scoping review method to map the results of the analysis from among the topics discussed. Article searches were performedon four databases—PubMed, Cochrane Library, Google Scholar, and Science Direct—using keywords with the Boolean Operators method. In addition, a manual search wasalso performed. The articles were selected with reference to the Preferred Reporting Items for Systematic Reviews and MetaAnalyses Extension for Scoping Review (PRISMA-ScR) flow in accordance with the predetermined inclusion and exclusion criteria. This led to the collection of 10 relevant articles, which were reviewed by reviewing the levels of IL-1β in an individual with aggressive periodontitis. In addition, how much bone damage occurs is seen through the depth of the pocket. Eight of ten articles showed a correlation between levels of IL-1β and bone loss in aggressive periodontitis. Elevated IL-1β levels in patients with aggressive periodontitis reveal a correlation with the severity of the disease that is bone loss.